2011
DOI: 10.1002/jsfa.4625
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bud load on quality of Beogradska besemena and Thompson seedless table grapes and cultivar differentiation based on chemometrics of analytical indices

Abstract: The results indicate that the effects of different bud loads are cultivar-dependent. Bud load and genotype differences were shown to dramatically impact the quality and antioxidant properties of table grape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Baiano & Terracone (2011) found no significant correlations between the phenolic distribution and the antioxidant activity of seeds and pulp. In any case, genotype differences dramatically impact the quality and antioxidant properties of table grapes (Baiano & Terracone, 2012).…”
Section: Chemical Analysismentioning
confidence: 99%
“…Baiano & Terracone (2011) found no significant correlations between the phenolic distribution and the antioxidant activity of seeds and pulp. In any case, genotype differences dramatically impact the quality and antioxidant properties of table grapes (Baiano & Terracone, 2012).…”
Section: Chemical Analysismentioning
confidence: 99%
“…Muscat aroma is greatly appreciated in grapes destined for fresh consumption and is directly related to monoterpenes, such as linalool, rose oxide, citral, geraniol, nerol and citronellol (Fenoll et al, 2009). Table grapes are a major source of health promoting bioactive compounds (Baiano and Terracone, 2012;Lutz et al, 2011). Colored grapes are the most active because of their richness in phenolic compounds with multiple biological effects and potential health benefits (Carrieri et al, 2013;Guerrero et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Coletta et al (2014) found that training system and bud load can affect the polyphenolic compounds concentration of the red wines, and therefore, the total antioxidant capacity. Baiano and Terracone (2012) concluded, that the changes in the quality of grapes by reducing the bud load were not always positive, i.e. by decreasing pulp antioxidant activity of cultivar 'Beogradska besemena'.…”
Section: Introductionmentioning
confidence: 96%
“…decreasing of bud fertility and fruitfulness, and reducing cluster weight (Fawzi et al 2010). However, researchers indicate that the effect of bud load is depended on cultivars/varieties, and therefore general recommendation for pruning intensity cannot be made (Bhosale et al 2010;Baiano and Terracone 2012;Coletta et al 2014). Various sensitivity to the pruning level probably depends mainly on different phenotypic behaviour (Baiano and Terracone 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation